TECHNOLOGICAL PROPERTIES OF NANODISPERSIONS BASED ON DER-330 EPOXY RESIN AND BS-50 FUMED SILICA - A. A. Pykhtin; I. D. Simonov-Emelyanov (Тонкие химические технологии)
The influence of silica dioxide nanoparticles in the form of fumed silica BS-50 on the rheological properties, residual shrinkage and shrinkage stresses upon curing an epoxy resin is considered. It is shown that the introduction of BS-50 in the optimum concentration of nanoparticles into DER-330 epoxy resin results in agglomeration, which is accompanied by an abnormal behavior of the disperse system with a decrease in viscosity by ~ 25%, ultimate shrinkage by ~ 15% and the level of residual stresses by a factor of ~ 4-10. These properties are manifested when the concentration of fumed silica is 0.05 vol. % The introduction of fumed silica slows the rise of residual stresses and increases the induction period from 2 to 4 hours. Depending on the mode of curing the minimum residual stress is observed at different concentrations of BS-50. At temperatures of 30ºC and 50°C concentration was 0.5 vol. %, and at 70°C - 0.05 vol. %. Curing at 30°C and 50°C result in a fall of residual stress by a factor of 12 and 4, respectively, at 70°C, by a factor of 4.